Governance for harmony in Asia and beyond - Tao, Julia Lai Po-Wah 1946-; Cheung, Anthony B.L.; Painter, Martin; Li, Chenyang (Milton Park, Abingdon, Oxon Routledge, 2010)
Harmony has become a major challenge for modern governance in the twenty-first century because of the multi-religious, multi-racial and multi-ethnic character of our increasingly globalized societies. Governments all over the world are facing growing pressure to integrate the many diverse elements and subcultures which make up modern pluralistic societies. This book examines the idea of harmony, and its place in politics and governance, both in theory and practice, in Asia, the West and elsewhere. It explores and analyses the meanings, mechanisms, dimensions and methodologies of harmony as a normative political ideal in both Western and Asian philosophical traditions.

The book argues that in Western political thought - which sees politics as primarily concerned with resolving social conflicts and protecting individual rights - the concept of harmony has often been neglected. In contrast, since earliest times harmony or ‘he’ has been a profound theme in Confucian thought, and current leaders of many East Asian governments, and the Chinese government, have explicitly declared that the realisation of a harmonious society is their aim. The book also assesses how harmony is pursued, jeopardized or deformed in the real world of politics, based upon empirical analysis of a variety of different cultural, social and political contexts, including: China, Hong Kong, Singapore, Malaysia, Singapore, Vietnam, Denmark, Latin America and the Scandinavian countries.

It shows how harmony as an organizing concept can help to promote new thinking in governance, and overcome problems of modern-day governance like distrust, adversarial conflicts, hyper-individualism, coercive state intervention, and free-market alienation. It also discusses the potential problems posed by the pursuit of harmony, in particular in the grave threat of totalitarianism, and considers how these risks could best be mitigated.
Part I. Introduction 1. Why Governance for Harmony? - Tao, Julia; Cheung, Anthony B.L.; Painter, Martin; Li, Chenyang Part II. Governance for Harmony in East--West Traditions 2. The Confucian Conception of Harmony - Yu, Kam Por 3. Harmony as a Guiding Principle for Governance - Li, Chenyang 4. Harmony in Government - Neville, Robert Cummings Part III. The Quest for Harmony in Government in Asia 5. Harmony, Conformity or Timidity? Singapore’s Overachievement in the Quest for Harmony - Barr, Michael D. 6. Harmony in Government--Society Governance: Problems, Challenges and Prospects in Malaysia - Nathan, K.S. 7. Risks in Adopting Modernization as the Way to Build a Harmonious Society in Modern China - Ouyang, Kang 8. Governance for Harmony: Challenges for Public Service Delivery Reform in China and Vietnam - Painter, Martin 9. Restoring Governability in Hong Kong: Managing Plurality and Joining Up Governance - Cheung, Anthony B.L. Part IV. The Quest for Harmony Beyond Asia: Interplay of Culture and Institution from Confucian and Liberal Perspectives 10. Open Politics and Disharmony - Rockman, Bert A. 11. Disharmony and Civil Society: A View from Latin America - Armony, Ariel C. 12. Consensual but Not Confucian: Resolving the Paradox of Consensual Politics in Scandinavia - Pierre, Jon 13. Harmony through Network Governance? - Torfing, Jacob 14. Can the Confucian Way Lead Us out of the Paradox of Trust in Democracy? - Tao, Julia 15. Propriety, Law and Harmony: A Functional Argument for the Rule of Virtue - Zhang, Qianfan 16. Xunzi’s Vision of Society: Harmony by Justice - Roetz, Heiner 17. Concordia versus Pax: The Impact of Eastern Governance for Harmony on Western Peace Concepts - Kumpfmüller, Karl A.
Includes bibliographical references and index.
Keywords: Peace-building.; Peace-building -- Asia; Harmony (Philosophy); Harmony (Philosophy) -- Religious aspects; Asia -- Politics and government -- 21st century